Pemanfaatan Kotoran Ternak Menjadi Biogas Skala Pilot plant dan Penerapannya sebagai Sumber Energi Alternatif Untuk Mendukung Green Farming di Daerah Tuban Desa Kebonagung - Moh. Midchol Afan; Miftahur Rohman; Yeni Anang Setiawan; Ahmad Yoga Dimam Abror; Cassablanca Firdaus (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The scarcity of subsidized fertilizers in Indonesia is spread evenly, one of the farmers who complained about the spike in prices for non-subsidized fertilizers and the scarcity of subsidized fertilizers was also experienced by farmers from Tuban District, Rengel District in Kebonagung Village, Kebonagung Village is a village where 40.3% of the residents have a livelihood. as farmers and breeders, farmers in fulfilling fertilizer rely on loans with quite high interest (Kadir, 2022). In Kebonagung village, the majority of residents still cultivate livestock in the traditional way, namely by releasing them and letting them go wild, creating problems including the large amount of livestock manure which causes environmental pollution in the village. Livestock can produce 12% waste by body weight and if not treated properly it will become waste and environmental pollution, because livestock manure contains NH3, NH and other compounds. this creates a new problem, namely an unpleasant and disturbing odor, the piled up waste will be disposed of after it dries up a little and is spread directly on their respective agricultural lands without any processing. The aim of this PKM is the utilization of cow manure waste into biogas as an alternative energy source. This activity was divided into three stages, namely the socialization stage, making biogas installations, and mentoring. PKM activities can have a good impact on the Kebonagung Ulusan village community so that environmental pollution can be resolved.